Less might be better. Sustainable funding strategies for cultural producers. Issue 2 (June 2016) - Cuccia, Tiziana; Rizzo, Ilde
Abstract: The Great Recession that has affected Western economies in these years imposes a radical change in the priorities of the public intervention in the national economies; among other effects, the severe public budget constraints in many European countries have generally caused a severe cut-back of public funds in the cultural sector. The different institutional contexts cultural producers face offer them different incentives; consequently, they can react to these "bad news" in different ways. In this paper we examine two possible directions to overcome these difficulties that are suggested from the information provided by key local witnesses: an individualistic direction, aimed at enlarging the supply of cultural services and to exploit market opportunities; a cooperative direction based on the creation of a network of cultural producers involved in projects stressing the social impact of their activities. Firstly, we sketch the costs imposed by the Great Recession on cultural producers in USA and Europe, looking at the different reactions. Secondly, we compare the different strategies cultural producers can adopt to face the crisis and differentiate the sources of their funds; we focus on the multi-product choice, and the creation of co-opetitive relations within a network. The analysis is based on the evidence offered by case studies concerning a group of cultural producers in Catania (Sicily, Italy). The investigation provides some policy suggestions on the kind of strategies to be promoted depending on the policy-maker's objectives and on the characteristics of the cultural producers. Highlights: The effects of the Great recession on cultural producers are examined. Two possible ways of overcoming the effect of Great recessions are considered: an individualistic way and a network way. The individualistic way includes the multi-product and multi-function choice, to enlarge the supply of services. The network way can assume different forms, and co-opetitive relations are specifically considered. Selected small cultural producers in Catania (Sicily, Italy) are taken as case studies.